Insulin-like growth factor-1 levels are associated with high comorbidity of metabolic disorders in obese subjects; a Japanese single-center, retrospective-study - Kubo, Haremaru; Sawada, Shojiro; Satoh, Michihiro; Asai, Yoichiro; Kodama, Shinjiro; Sato, Toshihiro; Tomiyama, Seitaro; Seike, Junro; Takahashi, Kei; Kaneko, Keizo; Imai, Junta; Katagiri, Hideki (Scientific reports, 2022)
Insulin like growth factor-1 (IGF-1) plays important roles in metabolic functions, especially in adulthood. Additionally, obese subjects are reportedly predisposed to having low absolute IGF-1 levels. However, the prevalence and clinical characteristics of obese subjects with low IGF-1 levels are unknown. We examined 64 obese subjects with a body mass index (BMI) ≥ 35 kg/m 2 , with no history of endocrinological disorders, receiving inpatient care. IGF-1 levels were interpreted based on the IGF-1 standard deviation score (SDS) clinically used and standardized by age and sex (low IGF-1 group; ≤ − 2.0 SDS and standard IGF-1 group; − 2.0 < and <  + 2.0 SDS). Notably, 26.6% of the subjects had low IGF-1. Body fat mass and percentage, but not BMI, were significantly higher in the low than in the standard IGF-1 group. Furthermore, natural log-transformed high-sensitivity C-reactive protein, and the frequencies of dyslipidemia and hyperuricemia were higher in the low IGF-1 group. Moreover, among the subjects without diabetes, fasting glucose levels were significantly higher in the low IGF-1 group. Stepwise variable selection procedure revealed body fat percentage to be a parameter most strongly associated with low IGF-1. Thus, low IGF-1 levels may be an important marker of adiposity-associated metabolic disorders in obese patients.